Pengaruh Pemberian Mesenchymal Stem Cell Wharton's Jelly Terhadap Aktivitas Enzim Katalase pada Tikus Wistar Model Hiperglikemia - Ramadhani, Dhea Amaliya (Faculty of Medicine, Universitas Andalas, 2024)
Objective: To determine the effect of Wharton's Jelly (MSC-WJ) mesenchymal stem cells on the activity of the catalase enzyme in hyperglycemic Wistar rats. Methods: This study used 21 male Wistar rats aged 2-3 months with a body weight of 200-300 grams according to the inclusion and exclusion criteria. Mice were divided into 3 groups: negative control (K-), positive control (K+), and treatment (P). Group K- was only given food and drink without being given treatment. The K+ group was injected intraperitoneally with alloxan at a dose of 100 mg/kg BW so that the rats became hyperglycemic. Group P was given an alloxan injection and left for a week, then given MSC-WJ 3x106 cells through the tail vein and left for four weeks. After four weeks, all groups had their blood taken to examine the catalase enzyme. Result: Mean of catalase activity enzyme in the K-, K+, and P groups were 4.22 ± 0.27 units/mg, 2.39 ± 0.19 units/mg, and 3.93 ± 0.45 units /mg, respectively. Conclusion: This shows that the administration of mesenchymal stem cells Wharton's Jelly (MSC-WJ) has an effect on increasing the serum catalase enzyme activity of Wistar rats with hyperglycemia models.